Openness and innovation - home and export demand effects on manufacturing innovation: Panel data evidence for Ireland and Switzerland - Martin Woerter; Stephen Roper (ETH Zurich, KOF Swiss Economic Institute, 2008)
Recent studies in the tradition of Schmookler have re-emphasised the potential role of demand in stimulating innovation. Here, we reconsider the role of home and export market demand in stimulating manufacturing innovation using comparable panel data for two small open economies - Ireland and Switzerland. Our analysis is based on the estimation of reduced form innovation production functions using panel data estimators over the sample period 1994 to 2005. For a range of innovation indicators, however, we find little evidence of any significant market demand effects, with innovation performance instead determined largely by firm-level capability effects and characteristics. In policy and strategy terms this suggests the continued value of measures to improve innovation capability regardless of market demand conditions. In more methodological terms our results suggest the validity of the usual assumption implicit in modelling innovation outputs that supply-side factors predominate.
Keywords: O3; O5; P5; 330; Innovation; demand; Ireland; Switzerland; Innovation; Gesamtwirtschaftliche Nachfrage; Industrieprodukt; Irland; Schweiz